2019
DOI: 10.1016/j.ejim.2019.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Patients with isolated pulmonary embolism in comparison to those with deep venous thrombosis. Differences in characteristics and clinical evolution

Abstract: Background: Patients with acute pulmonary embolism (PE) often have leg deep vein thrombosis (DVT); sometimes, however, a DVT is not detected (isolated PE, I-PE). We aimed at assessing the proportion of patients with I-PE, and their characteristics and clinical evolution compared to those with DVT with/without PE (DVT/PE). Methods: Among 3573 patients included in the START2-Register for a venous thromboembolic event, 2880 (80.6%) had DVT/PE, the remaining I-PE (19.4%). Results: Patients with I-PE were older [(≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 35 publications
3
38
1
1
Order By: Relevance
“… 5 The discrepancy between the frequencies of pulmonary embolism and DVT is surprising, because, although pulmonary embolism may occur in the absence of detectable DVT, this happens in only approximately 20% of studied patients. 10 Therefore, we question whether the observed pulmonary vessels occlusions that have been described in reports on COVID-19 patients are exclusively caused by pulmonary embolism. In our experience and in some reports, 11 12 filling defects of pulmonary vessels that are detected by CTA scans are in many instances more reminiscent of pulmonary thrombi rather than emboli, because they are not fully occlusive.…”
mentioning
confidence: 99%
“… 5 The discrepancy between the frequencies of pulmonary embolism and DVT is surprising, because, although pulmonary embolism may occur in the absence of detectable DVT, this happens in only approximately 20% of studied patients. 10 Therefore, we question whether the observed pulmonary vessels occlusions that have been described in reports on COVID-19 patients are exclusively caused by pulmonary embolism. In our experience and in some reports, 11 12 filling defects of pulmonary vessels that are detected by CTA scans are in many instances more reminiscent of pulmonary thrombi rather than emboli, because they are not fully occlusive.…”
mentioning
confidence: 99%
“…PE in the absence of a DVT (isolated pulmonary embolism (i-PE)) became the focus of recent research which identified a distinct clinical and risk profile for i-PE among 3573 patients of the START2 registry. 6 Importantly, 20% fulfilled the criteria of i-PE without DVTs in the general population. Multivariate analysis revealed that older age (>75 years), female sex, heart failure or cancer, and the absence of thrombophilic alterations are risk factors.…”
Section: Editorialmentioning
confidence: 97%
“…The findings of the study are consistent with registry data, suggesting an increased incidence of arterial events among those with isolated PE. 3 Further analysis of registry and additional prospective study would be useful to confirm the relationship between isolated PE and arterial thrombotic events.…”
mentioning
confidence: 99%
“…However, in a substantial portion of patients with PE, there is no DVT evident at the time of diagnosis. [1][2][3] This increasingly recognized clinical entity has been termed isolated PE. Isolated PEs are frequently small, nonocclusive thrombi located in segmental or subsegmental pulmonary arteries and may be discovered incidentally.…”
mentioning
confidence: 99%
See 1 more Smart Citation